Early retirement eligibility and employment behavior: evidence from a cohort based pension reform - Clara Welteke; Johannes Geyer; Peter Haan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyzes the employment effects of a major pension reform in Germany using cohort discontinuities. In particular, we focus on the abolition of an early retirement option for women. Up until cohort 1951 women could draw old-age pensions starting with age 60. Women born after 1951 no longer had this opportunity. The eligibility age for early retirement was increased to 63. We exploit this reform in a regression discontinuity framework to study the effects on employment and program substitution. Our preliminary results suggest that the increase in the eligibility age for early retirement increased employment rates of older women. Remarkably, we do not find any significant spillover effects into alternative paths to exit the labor force. On the contrary, we find negative effects on reduced earnings capacity pension participation rates, and small insignificant effects on the unemployment rate of 60 year-old women. Furthermore, we find negative effects on social security program participation of women in their late 50s.
Keywords: J14; J26; J22; 330